Hypercholesterolemia diagnosis, treatment patterns and target achievement in patients with acute coronary syndromes in Germany - Gitt, Anselm Kai; Parhofer, Klaus G.; Laufs, Ulrich; März, Winfried; Paar, W. Dieter; Bramlage, Peter; Marx, Nikolaus (Clinical research in cardiology, 2023)
Patients who experience an acute coronary syndrome (ACS) are at high risk of further cardiovascular events. Long-term treatment of cardiovascular risk factors, such as hyperlipidemia, is critical to prevent progression of coronary heart disease. However, many patients do not reach recommended target levels for low-density lipoprotein (LDL) cholesterol, despite receiving lipid-lowering therapy.
Online veröffentlicht: 17. September 2022
Gesehen am 24.06.2024